Energy Efficient VM Placement for Effective Resource Utilization using Modified Binary PSO. (21st November 2017) - Tripathi, Atul; Pathak, Isha; Vidyarthi, Deo Prakash
Abstract: In Virtualized data center for implementing cloud, mapping of virtual machines (VM) on to physical machines aims to efficiently utilize the resources of the physical machines in order to earn better profit for the cloud provider. Energy is an important parameter for the huge virtualized data center and is to be minimized as much as possible while VM placement. The proposed work addresses two important Cloud aspects: efficient energy usage and effective resource utilization. For this, modified binary particle swarm optimization is proposed and applied for the VM placement problem. The simulation experiments, carried out to evaluate the performance of the proposed model, prove that the proposed approach results in reduced energy consumption with least resource wastage compared with some other contemporary methods proposed in the literature.